Evidence of exposure of domestic pigs to Highly Pathogenic Avian Influenza H5N1 in Nigeria - Meseko, Clement (Sci Rep, 2018)
Avian influenza viruses (AIV) potentially transmit to swine as shown by experiments, where further reassortment may contribute to the generation of pandemic strains. Associated risks of AIV inter-species transmission are greater in countries like Nigeria with recurrent epidemics of highly pathogenic AI (HPAI) in poultry and significant pig population. Analysis of 129 tracheal swab specimens collected from apparently healthy pigs at slaughterhouse during presence of HPAI virus H5N1 in poultry in Nigeria for influenza A by RT-qPCR yielded 43 positive samples. Twenty-two could be determined by clade specific RT-qPCR as belonging to the H5N1 clade 2.3.2.1c and confirmed by partial hemagglutinin (HA) sequence analysis. In addition, 500 swine sera were screened for antibodies against influenza A virus nucleoprotein and H5 HA using competition ELISAs and hemagglutination inhibition (HI) tests. Serologically, 222 (44.4%) and 42 (8.4%) sera were positive for influenza A virus NP and H5 antibodies, respectively. Sera reacted to H5N1 and A/H1N1pdm09 strains by HI suggesting exposure of the Nigerian domestic pig population to these viruses. We report for the first time in Nigeria, exposure of domestic pigs to H5N1 virus. This poses potential public health and pandemic risk due to interspecies transmission of avian and human influenza viruses.